A brief overview on radon measurements in drinking water. (July 2017) - Jobbágy, Viktor; Altzitzoglou, Timotheos; Malo, Petya; Tanner, Vesa; Hult, Mikael
Abstract: The aim of this paper is to present information about currently used standard and routine methods for radon analysis in drinking waters. An overview is given about the current situation and the performance of different measurement methods based on literature data. The following parameters are compared and discussed: initial sample volume and sample preparation, detection systems, minimum detectable activity, counting efficiency, interferences, measurement uncertainty, sample capacity and overall turnaround time. Moreover, the parametric levels for radon in drinking water from the different legislations and directives/guidelines on radon are presented. Highlights: Literature data on radon content in different waters is collected from Europe. International radon guidance and parametric values in drinking water are presented. An overview is given on the most common water radon measurement techniques. Parameters affecting measurement results are discussed. Each of the discussed methods seems to be adequate for radon in water measurements.